B‐lymphocyte–intrinsic and –extrinsic defects in secretory immunoglobulin A production in the neural crest–conditional deletion of endothelin receptor B model of Hirschsprung‐associated enterocolitis. Issue 6 (25th March 2019) - Medrano, Giuliana; Cailleux, Frederic; Guan, Peihong; Kuruvilla, Korah; Barlow-Anacker, Amanda J.; Gosain, Ankush
ABSTRACT: Hirschsprung disease (HSCR) is a common cause of intestinal obstruction in the newborn. Hirschsprung‐associated enterocolitis (HAEC) is a significant and life‐threatening complication of HSCR, affecting up to 60% of patients. Animal models of endothelin receptor B ( EdnrB ) mutation reliably model human HSCR and HAEC. We previously demonstrated intestinal dysbiosis and a gut‐specific deficiency of B‐lymphocyte–produced secretory IgA (sIgA), the primary effector molecule of mucosal immunity, in mice with homozygous neural crest cell–conditional deletion of EdnrB ( EdnrB NCC −/− ). To determine mechanisms for sIgA deficiency, we examined intrinsic and extrinsic aspects of B‐lymphocyte development and function. Expression of the endothelin axis components [endothelin‐1 ( ET‐1 ), endothelin‐3 ( ET‐3 ), endothelin receptor A ( EdnrA ), EdnrB ] were determined over a developmental time course. B‐lymphocyte survival and Ig production were assayed in vitro . Polymeric Ig receptor (pIgR)–mediated IgA transport into the intestinal lumen was interrogated. We found endothelin axis component ( EdnrA, EdnrB, ET‐1, ET‐3 ) expression in developing extramedullary hematopoietic organs and that some splenic B lymphocytes express EdnrB . Splenic B lymphocytes from EdnrB NCC −/− mice showed no intrinsic defect in survival vs . wild‐type (WT) B lymphocytes. In vitro stimulation of splenic B lymphocytes demonstrated decreased IgA, IgG, and IgM production in EdnrB NCC −/− vs . WT mice. Additionally, small intestinal pIgR was decreased ∼50% in EdnrB NCC −/− mice. These results suggest an intrinsic B‐lymphocyte defect in antibody production as well as an extrinsic defect in IgA transport in the EdnrB NCC −/− model of HAEC. Our results are consistent with human HAEC observations of decreased luminal sIgA and mouse models of other inflammatory bowel diseases, in which decreased pIgR is seen in concert with a dysregulated microbiota. Finally, our results suggest targeting the dysbiotic microbiome and pIgR‐mediated sIgA transport as potential therapeutic approaches in prevention and treatment of HAEC.—Medrano, G., Cailleux, F., Guan, P., Kuruvilla, K., Barlow‐Anacker, A. J., Gosain, A. B‐lymphocyte–intrinsic and –extrinsic defects in secretory immunoglobulinA production in the neural crest–conditional deletion of endothelin receptor B model of Hirschsprung‐associated enterocolitis. FASEB J. 33, 7615–7624 (2019). www.fasebj.org